Effect of dairy milk, eggs, meat, fish and fruits intake on academic performances of secondary school students in Bangladesh (Bangladesh Journal of Medical Science, 2018)
Background: Contribution of dairy milk and other food items and schools to academic performances of students are the important factors to build a peaceful meritorious nation with sound mental and physical health.Objective: This experiment was designed to study the contribution of dairy milk and other food item intake pattern and schools to academic performances.Method: Students of class nine in Bangladesh were enumerated using a preprescribed questionnaire during March 2016 to June 2016 by direct interview method. Collected primary data were analyzed using the Statistical Package for the Social Sciences version 14.015.Results: Male (69.63%) students and students of schools in the town (84.97%) performed better. Majority of the students in towns (46.85%; 49.65%) and villages (45.51%; 50.90%) drank dairy milk and ate meat respectively, once or twice in a week. Many students in towns (30.77%) and villages (38.92%) ate eggs for 3 to 4 days in a week. Maximum students in town (53.50%) and in village (46.71%) took fish for 5 to 7 days and 3 to 4 days in a week, respectively. Many students in town (39.86%) and in village (59.88%) took fruits 1 to 2 days and 5 to 7 days in a week, respectively. Most (74.31%) of the students who took dairy milk, meat (73.68%), fruits (66.67%), fish (65.81%) and eggs (64.71%) everyday in a week obtained A grade.Conclusions: Schools, availability of dairy milk, meat, fruits, fish and eggs, Tiffin intake status and gender affected the academic performances but educational institutions had no effect on weekly dairy milk, eggs and meat intake of the students but weekly fish and fruits intake status were affected.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.355-359